PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL MATA DIKLAT MENERAPKAN MATERIAL FINISHING BANGUNAN KELAS XI DI SMK NEGERI 1 KOTO XI TARUSAN - 1060-1081 , Eka Winda Rianti (Universitas Negeri Padang, 2016)
ABSTRACTThe purpose of this research was to determine whether there was effects of cooperative learning model type STAD on learning outcomes of 'applying construction finishing material' subjectat class XI students TGB majoring SMKN 1 Koto XI Tarusan.This research was true experimental research with pretest-posttest control group design. The results showed in experimental class with an average score of pretest and posttest were 73 and 86 respectively, where as in control class average score of pretest and posttest were 65 and 76 respectively. It can be seen that there was an improvement ofstudent’s learning outcomes in experimental class. Then, t-test obtained thitung = 0.876 and ttabel = 2.060 at 0.05 signification. It can be concluded that the application of cooperative learning model type STAD does not give significant impact on learning outcomes of 'applying construction finishing material' subject. Keywords: Kooperatif tipe STAD, Hasil Belajar, Menerapkan MaterialFinishing Bangunan